Physical Activity in Natural Environments Is Associated with Motivational Climate and the Prevention of Harmful Habits: Structural Equation Analysis - Cofre-Bolados, C (Frontiers Media S.A., 2019)
Background: Practicing physical activity in a natural environment has various benefits that make it an ideal setting to develop healthy behaviors and thereby diminish unhealthy habits. The objective of this study was to develop and verify an explicative model for motivational climate in sport, considering its potential influence on alcohol and tobacco consumption. Methods: The study included 2273 adolescents from Granada (Spain), analyzing motivational climate (PMCSQ-2), alcohol consumption (AUDIT) and tobacco consumption (FTND). Multi-group structural equation modeling was conducted, yielding an excellent fit (χ2 = 168.170; gl = 32; p = 0.00; CFI = 0.972; NFI = 0.966; IFI = 0.972; RMSEA = 0.045). Results: The main findings were: a negative relationship between task climate and alcohol consumption among students practicing physical activities in a natural environment; a positive relationship between ego climate and alcohol consumption among those practicing other types of physical activity; and a positive and direct relationship between alcohol and tobacco consumption, which was stronger among those who did not practice physical activity in a natural environment. Conclusion: We conclude that physical-sport activity practiced in nature is a key to acquiring healthy patterns characterized by intrinsic motivations in sport and lower consumption of harmful substances. © 2019 Castro-Sánchez, Zurita-Ortega, Pérez-Turpin, Cachón-Zagalaz, Cofre-Bolados, Suarez-Llorca and Chacón-Cuberos.